2000
DOI: 10.1046/j.1440-1819.2000.00752.x
|View full text |Cite
|
Sign up to set email alerts
|

Depression among caregivers of the frail elderly in urban Japan

Abstract: A cross-sectional study was conducted in order to investigate the various factors related to the depression in caregivers of the elderly in need of care in urban Japan. The caregivers answered a self-administered questionnaire about various factors that may affect their depression, and also completed a Center for Epidemiologic Studies Depression Scale evaluation (CES-D). Compared with non-depressed caregivers, depressed caregivers attended the elderly longer, while time spent for physical caregiving did not di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
2
3
0
1
Order By: Relevance
“…The average age of caregivers was 63.5 years, of whom 67.7 % were women. The average level of caregivers' burden in JZBI scores was 37.0 points, and 42.9 % of the caregivers suffered from depressive symptoms, which are comparable with the findings of previous studies [8,10,25,26].…”
Section: Resultssupporting
confidence: 89%
“…The average age of caregivers was 63.5 years, of whom 67.7 % were women. The average level of caregivers' burden in JZBI scores was 37.0 points, and 42.9 % of the caregivers suffered from depressive symptoms, which are comparable with the findings of previous studies [8,10,25,26].…”
Section: Resultssupporting
confidence: 89%
“…In contrast, family size emerged as a weak negative correlate of burden, confirming the results of other studies (Lee & Sung, 1998). Finally, the extent of caregiving was the only background variable that had a direct positive effect on depression, as confirmed among other populations as well (Matsuu et al, 2000;Yates et al, 1999). Our results showed that sense of mastery was the major (negative) predictor of depression among ArabIsraeli caregivers, as has been reported among other populations (Clair et al, 1995;Pioli, 2010;Rozario & DeRienzis, 2008;Sherwood et al, 2007;Yates et al, 1999).…”
Section: Discussionsupporting
confidence: 90%
“…Finally, characteristics related to the extent of the care provided can influence depression directly and indirectly. A greater number of caregiving hours directly increases the level of depression among family caregivers (Matsuu, Washio, Arai, & Ide, 2000;Yates et al, 1999). Caregiving hours are also positively correlated with caregiving burden (Riedel, Fredman, & Langenberg, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Segundo Matsuu et al (2000), a alta prevalência de depressão entre os cuidadores de idosos pode estar associada ao tempo despendido com os cuidados ao idoso. Aqueles cuidadores que atendem aos idosos durante vários dias do mês e por várias horas no dia diminuem seu tempo para visitar amigos e/ou relaxar, e têm maiores chances de apresentar episódios de depressão.…”
Section: O Adoecimento Relacionado Ao Trabalhounclassified